High-dose therapy with peripheral blood stem cell transplantation for patients with relapsed or refractory Hodgkin's disease: long-term outcome and prognostic factors - Neben, Kai; Hohaus, Stefan; Goldschmidt, Hartmut; Egerer, Gerlinde; Voso, Maria Teresa; Ho, Anthony Dick; Haas, Rainer (Annals of hematology, 2000)
From March 1986 to March 1998, 82 patients with relapsed or refractory Hodgkin's disease underwent high-dose chemotherapy (HDCT) with peripheral blood stem cell (PBSC) transplantation in our center. This is a retrospective analysis of the long-term clinical outcome. There were 52 males and 30 females with a median age of 32 years (range 18-59 years). Prior to transplantation, 36 patients were in complete remission (CR), 34 in partial remission (PR), and 12 had refractory disease after salvage therapy. For HDCT, 78 patients were treated with CBV (cyclophosphamide, 6.0-6.8 g/m2; etoposide, 1.0-1.6 g/m2; carmustine, 0.45-0.8 g/m2), while four patients received different regimens. Probability of freedom from progression (FFP), overall survival (OS), and event-free survival (EFS) at 5 years of the entire group was 63%, 61%, and 54%, respectively. Early mortality rate (≤100 days) declined from 17% to 6% after 1992. Five patients died of late transplant-related complications (>100 days), including secondary lymphoma and leukemia in two patients. None of the refractory patients survived beyond 3.5 years. Multivariate analyses identified extranodal sites of disease at relapse and refractory disease status prior to transplantation as significant prognostic factors for FFP, EFS, and OS. As we have shown in our study, remarkable progress was achieved in reducing early morbidity and mortality over time, but this was associated with only a slight, not significant improvement of long-term outcome (OS 66% vs 57% at 5 years for patients undergoing PBSC transplantation before and after 1992, P=0.26). Although the results as a whole are encouraging for chemosensitive patients, new therapeutic strategies are needed to reduce toxicity and improve the clinical outcome of patients, especially of those with a less favorable prognosis.
Gesehen am 21.12.2021